Statut socio-économique et utilisation des services de santé à Montréal - Siemiatycki, Jack; Richardson, Lesley (L'Actualité économique)

(untitled) (HEC Montréal, 1980)
AbstractNational health insurance was implemented in Quebec in late 1970. Previously reported surveys carried out in Montreal in 1969-70 and 1971-72 showed that while there was no change in overall volume of services, there was a redistribution, with increases among the poor and decreases among the wealthy. We conducted a survey in late 1974 to determine the "steady-state" impact of l’assurance-maladie on social class differences in health care utilization. In a socially heterogeneous area of Montreal 1,559 households were surveyed. When reported morbidity status was taken into account, physician visit rates in the past two weeks were 21.6 per cent, 20.2 per cent, and 20.4 per cent in low, middle and high economic classes respectively, confirming the disparity of access has been reduced. However, relative to the non-poor, the poor still made considerable use of hospital clinics and emergency rooms for primary care and more of their visits entailed prescriptions and physician-initiated requests to return. The latter may indicate that the poor still consult the doctor for more advanced conditions than the non-poor. There is no evidence of abuse of "free" medical care by the poor. In contrast to the equalization in use of physician services, dental services are still unequally distributed, although compared with the 1969-70 and 1971-72 surveys, utilization rates were higher in 1974 in all social classes. The overall increase in per capita physician visits was confirmed by statistics of the Régie de l’assurance-maladie du Québec. A parallel increase in the supply of physicians kept the workload of the average physician at a constant level.